Differences in Expression, Content, and Activity of 11β-HSD1 in Adipose Tissue between Obese Men and Women. (9th December 2012) - Torres, A.; Iñiguez, G.; Ferrario, M.; Mericq, V.
Abstract : Cortisol production in adipose tissue is regulated by 11 β -HSD1. Objective . To determine whether there are differences in gene expression, enzyme activity, and protein content of the 11 β -HSD1 enzyme in VAT (visceral adipose tissue) and SAT (subcutaneous adipose tissue) from obese compared to nonobese adults. Methods . VAT and SAT samples were obtained from 32 obese subjects (BMI > 30  Kg/m 2 ) who underwent bariatric surgery and 15 samples from controls submitted to elective surgery. Fasting serum glucose, insulin, and lipids were measured. The expression of 11 β -HSD1 was determined by RT-PCR, the enzyme activity by thin-layer chromatography, and the protein content by Western blot. Results . Obese patients had higher cholesterol, insulin, and HOMA-IR compared to nonobese. There were no differences in VAT or SAT expression of 11 β -HSD1 between obese and nonobese patients. However, we found lower 11 β -HSD1 activity and protein content in VAT, in obese women versus nonobese women (P < 0.05 ). BMI and 11 β -HSD1 enzyme activity and protein content in VAT correlated inversely in women. Conclusions . Regulation of 11 β -HSD1 activity in VAT from obese subjects appears to be gender specific, suggesting the existence of a possible protective mechanism modulating this enzyme activity leading to a decrease in the production of cortisol in this tissue.